The Use of Cognitive Mapping Technique in Management Research: Theory and Practice - Rusli, Ahmad; Noor Azman, Ali (MCB UP Ltd, 2003)
The purpose of this article is to analyse the use of a qualitative approach using cognitive mapping techniques in the study of a decision‐making process. This study takes place in a public sector and in the context of a performance appraisal system (PAS). This is in line with recommendations by scholars and researchers to conduct a management research in a public service context (see Brown, 1999; Bissessar, 2000; Jabroun and Balakrishnan, 2000; O’Donnell and O’Brien, 2000; Redman, Snape and Thompson, 2000). This article also intends to elucidate and justify the methodological approach used, examine the assumptions underlying the use of a particular research design, and provide arguments for the preference of the methodology used. It is hoped that this will contribute to the understanding of the nature and validity of the research undertaken. This article begins by reviewing the theoretical issues of the research framework, the main features of the qualitative methodologies, and finally, the research method applied in this research is determined and justified.